2005
DOI: 10.1080/00049158.2005.10674971
|View full text |Cite
|
Sign up to set email alerts
|

Bell-miner-associated dieback at the tree crown scale: a multi-trophic process

Abstract: This paper examines some of the factors and processes which interact within eucalypt stands affected by bell-miner-associated dieback. A key symptom of this form of dieback is sustained foliar damage from herbivorous insects. in particular psyllids. Repeated cycles of defoliation/refoliation result in branch death and crown contraction. Weakened trees become more susceptible to secondary stressors such as wood borers. soil fungal pathogens and abnormal levels of soil moisture. Psyllid outbreaks can occur throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Our work suggests that bell miners are not only defending psyllids, as previously suggested as being their primary food source, but also the entire insect population that is fed to their young throughout the year [12] [43] [69] [70]. Our findings are consistent with the suggestion that bell miners are opportunistic and utilise areas that contain high levels of lerp but also other insect species that supplement their diet [42] [43].…”
Section: Discussionsupporting
confidence: 82%
“…Our work suggests that bell miners are not only defending psyllids, as previously suggested as being their primary food source, but also the entire insect population that is fed to their young throughout the year [12] [43] [69] [70]. Our findings are consistent with the suggestion that bell miners are opportunistic and utilise areas that contain high levels of lerp but also other insect species that supplement their diet [42] [43].…”
Section: Discussionsupporting
confidence: 82%
“…Granger et al (1994) reported tree decline in E. ovata and E. camphora communities where the soils had lowered C/N ratio, increased mineral N and increased foliar N concentrations. In NSW, Stone (2005) reported a relationship between soil N content and poor health of eucalypts although a relationship was reported with inherent soil fertility rather than as a result of reducing the frequency of fire. In a small study near Sydney, Stone and Simpson (2006) reported a weak correlation between poor eucalypt health and increasing soil N although there were confounding factors of geology, topography and land management.…”
Section: Discussionmentioning
confidence: 91%
“…(After low intensity fires, mineral nitrogen released by heating soil organic matter is quickly taken up into standing biomass [8]). Decline is consistently associated with high levels of nitrogen and low carbon:nitrogen ratios in soils but it is not related to the floristic composition of the understorey (for example, [11]). In temperate areas where the climate is not suitable for lantana, native shrubs are mostly involved in the process [4].…”
Section: Invasions In Eucalypt Systemsmentioning
confidence: 99%